1999
DOI: 10.1073/pnas.96.20.11382
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative mutation in the β2 and β6 proteasome subunit genes affect alternative cell fate decisions in the Drosophila sense organ lineage

Abstract: In Drosophila, dominant-negative mutations in the ␤2 and ␤6 proteasome catalytic subunit genes have been identified as dominant temperature-sensitive (DTS) mutations. At restrictive temperature, ␤2 and ␤6 DTS mutations confer lethality at the pupal stage. I investigate here the role of proteasome activity in regulating cell fate decisions in the sense organ lineage at the early pupal stage. Temperatureshift experiments in ␤2 and ␤6 DTS mutant pupae occasionally resulted in external sense organs with two socket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 34 publications
(29 reference statements)
4
66
0
2
Order By: Relevance
“…), RNAi or pharmacological inhibition have been used to study proteasome function. 8,22,27,51,57,64 In other approaches, whole embryos mutant for proteasome subunits were characterized for defects in dendrite pruning in sensory neurons in Drosophila. [65][66][67] However, a specific analysis characterizing recessive alleles for defects in proteasome activity has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…), RNAi or pharmacological inhibition have been used to study proteasome function. 8,22,27,51,57,64 In other approaches, whole embryos mutant for proteasome subunits were characterized for defects in dendrite pruning in sensory neurons in Drosophila. [65][66][67] However, a specific analysis characterizing recessive alleles for defects in proteasome activity has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome-mediated protein degradation has previously been implicated in other systems as a regulatory mechanism controlling the level of Notch signaling. For example, dominant-negative temperature-sensitive mutations in two Drosophila proteasome subunits result in shaft-to-socket cell fate transformations and a double-socket phenotype; both of these phenotypes are associated with an increase in Notch signaling (Schweisguth 1999). The increase in Notch signaling observed in these dominant-negative proteasome subunit mutations in Drosophila is likely due, at least in part, to a decrease in degradation of the cleaved intracellular form of the Notch receptor; an activated version of the intracellular domain is stabilized in one of the dominant-negative proteasome subunit mutants (Schweisguth 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dominant-negative temperature-sensitive mutations in two Drosophila proteasome subunits result in shaft-to-socket cell fate transformations and a double-socket phenotype; both of these phenotypes are associated with an increase in Notch signaling (Schweisguth 1999). The increase in Notch signaling observed in these dominant-negative proteasome subunit mutations in Drosophila is likely due, at least in part, to a decrease in degradation of the cleaved intracellular form of the Notch receptor; an activated version of the intracellular domain is stabilized in one of the dominant-negative proteasome subunit mutants (Schweisguth 1999). Proteasome-mediated degradation of the intracellular domain of the Notch receptor has also been shown or suggested to occur in other systems, including C. elegans (Mango et al 1991;Hubbard et al 1997;Gupta-Rossi et al 2001;Oberg et al 2001;Wu et al 2001;McGill and McGlade 2003;Tsunematsu et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant subunits act in a dominant negative manner to interfere with proteasome function; in multiple previous studies, they have been shown to inhibit UPS-mediated degradation of known proteasome substrates (Schweisguth, 1999;Speese et al, 2003;Neuburger et al, 2006). Transgenic co-expression of both proteasome subunit mutants in the Drosophila eye using the UAS-GAL4 system has a synergistic effect (Belote JM and Fortier, 2002).…”
Section: Resultsmentioning
confidence: 99%